The Influence of Functionality, E-WOM, and Interactive Features on User Loyalty Mediated by Trust Levels in The “Tentang Anak” Application - Maria, Leticia; Winoto, Herry; Fushen, Fushen (Journal of Applied Business, Taxation and Economics Research, 2026)
This study analyzes the influence of functionality, electronic word of mouth (E-WOM), and interactive features on user loyalty mediated by trust in the 'Tentang Anak' application. A quantitative approach using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method was applied to 125 respondents. The results show that functionality and E-WOM have a significant effect on loyalty, while interactive features have a positive effect on trust. Trust also acts as a partial mediator between interactive features and user loyalty. These findings emphasize the importance of trust in increasing user loyalty to digital health applications.